Mobile sex-tech apps: How use differs across global areas of high and low gender equality - Gesselman, Amanda N.; Druet, Anna; Vitzthum, Virginia J. (PLOS ONE, 2020)
Digital technologies are increasingly intertwined into people’s sexual lives, with growing scholarly interest in the intersection of sex and technology (sex–tech). However, much of the literature is limited by its over emphasis on negative outcomes and the predominance of work by and about North Americans, creating the impression that sex–tech is largely a Western phenomenon. Based on responses from 130,885 women in 191 countries, we assessed how women around the world interact with mobile technology for sex-related purposes, and whether in areas of greater gender inequality, technological accessibility may be empowering women with knowledge about sexuality. We investigated women’s use of technology to find sexual partners, learn about sex and improve their sexual relationships, and track their own sexual health. About one-fifth reported using mobile apps to find sexual partners. This use varied by region: about one-third in Oceania, one-fourth in Europe and the Americas, and one-fifth in Asia and Africa. Staying connected when apart was the most commonly selected reason for app use with a sexual partner. About one-third had used an app to track their own sexual activity. Very few reported that the app they used to improve their sexual relationships was detrimental (0.2%) or not useful (0.6%). Women in countries with greater gender inequality were less likely to have used mobile apps to find a sexual partner, but nearly four times more likely to have engaged in sending and receiving sexts. To our knowledge, this study provides the most comprehensive global data on sex–tech use thus far, demonstrates significant regional variations in sex-tech use, and is the first to examine women’s engagement in sex-related mobile technology in locations with greater gender disparities. These findings may inform large-scale targeted studies, interventions, and sex education to improve the lives of women around the world.